Long-Range Coulomb Forces in DIS: Missed Radiative Corrections? - Kopeliovich, B. Z; Tarasov, A. V; Voskresenskaya, O. O (2001)
Eur.Phys.J. A11 (2001) 345-356 The Born approximation, one photon exchange, used for DIS is subject to virtual radiative corrections which are related to the long-range Coulomb forces. They may be sizeable for heavy nuclei since Z is not a small parameter. So far these corrections are known only for two processes, elastic scattering and bremsstrahlung on the Coulomb field of a point-like target. While the former amplitude acquires only a phase, in the latter case the cross section is modified also. Although the problem of Coulomb corrections for DIS on nuclei is extremely difficult, it should be challenged rather than 'swept under the carpet'. The importance of these radiative corrections is questioned in present paper. We show that in the simplest case of a constant hadronic current the Coulomb corrections provide a phase to the Born amplitude, therefore the cross section remains the same. Inclusion of more realistic hadronic dynamics changes this conclusion. The example of coherent production of vector mesons off nuclei reveals large effects. So far a little progress has been made deriving exact lepton wave functions in the Coulomb field of an extended target. Employing available results based on the first-order approximation in Z we conclude that the Coulomb corrections are still important for heavy nuclei. We also consider an alternative approach for extended nuclear targets, the eikonal approximation, which we demonstrate to reproduce the known exact results for Coulomb corrections. Calculating electroproduction of vector mesons we again arrive at a large deviation from the Born approximation. We conclude that one should accept with caution the experimental results for nuclear effects in DIS based on analyses done in the Born approximation.